Student’s Preferences in the Selection of Online Shopping Goods Delivery Services - Munajat Tri Nugroho; Purwo Setiawan; Octalia Rahmasari (Jurnal Ilmiah Teknik Industri, 2021)
(The rise of e-commerce or online shops has made the number of shipping service companies increase. Delivery service companies need to analyze consumer preferences in selecting delivery services when shopping online so that they can continue to compete. This study aims to analyze the attributes or important factors that influence consumers and how much influence these factors have on consumer preferences. The AHP (Analytical Hierarchy Process) method is used to obtain the important factors and the discrete choice method with the multinomial logit model to analyze the influence of factors on consumer preferences. With the AHP method, three important attributes are obtained including cost with a value of 4.248, insurance with a value of 1.729, and delivery time with a value of 1.471. Judging from the influence on preferences, the cost factor and delivery time have a negative effect, which means that the lower the rate and the faster the time will increase customer satisfaction. While the insurance factor has a positive effect, which means that consumers prefer insurance. The most influential factor is cost with a parameter value of -1.97, then insurance with a parameter value of 1.66, and finally delivery time with a parameter value of -0.564. Based on gender, the results show that women's considerations of the cost attribute are higher than men's considerations. Meanwhile, based on allowance, the higher the allowance, the more important insurance and delivery time are considered.